1992
DOI: 10.1080/09553009214552171
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Electrolysis and Methylene Blue Photodynamic Action inEscherichia Coli

Abstract: There is interest in the use of photodynamic therapy for the treatment of certain diseases, including cancer. However, weak penetration of visible light in tissues has restricted its use. In this study the possibility of enhancing photodynamic effects by the use of energies that penetrate more deeply in tissues was investigated. Weak electric currents (1.0 mA) applied to Escherichia coli cells for short periods, producing little or no lethal damage, was found to act synergistically with the photodynamic action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In previous studies, we have demonstrated that treatment of bacterial and tumoral cells in a single chamber can induce several cellular effects, such as alterations in cell surface composition and cell viability [Capella and Menezes, 1992;Holandino et al, 1998;2000]. In previous studies, we have demonstrated that treatment of bacterial and tumoral cells in a single chamber can induce several cellular effects, such as alterations in cell surface composition and cell viability [Capella and Menezes, 1992;Holandino et al, 1998;2000].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we have demonstrated that treatment of bacterial and tumoral cells in a single chamber can induce several cellular effects, such as alterations in cell surface composition and cell viability [Capella and Menezes, 1992;Holandino et al, 1998;2000]. In previous studies, we have demonstrated that treatment of bacterial and tumoral cells in a single chamber can induce several cellular effects, such as alterations in cell surface composition and cell viability [Capella and Menezes, 1992;Holandino et al, 1998;2000].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Capella and Menezes [1992] used the cationized ferritin technique and determination of the zeta potential to demonstrate that treatment of Escherichia coli with electricity also promoted loss of membrane negative charges. Ruthenium staining showed that cathodic treatment caused loss of anionogenic sites in parallel with the occurrence of cell lysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, scientists are searching for ways of increasing the selectivity and accumulation of photosensitizers in infectious agents, according to the general concept of PDT treatment of tumors. In this way, increased PDT effects over in vivo Escherichia coli , were observed when methylene-blue-based was employed in combination with a 1-mA electric current [ 169 ] or when a previous laser irradiation was applied. Similarly, the antimicrobial PDT efficiency was increased by employing photosensitizers conjugated with antibodies, such as chlorin e6 linked to poly-L-lysine, which showed a high in vitro efficiency against the pathogenic microflora of the oral cavity [ 170 ].…”
Section: Crossed and Linked Histories Of Tetrapyrrolic Or How Natumentioning
confidence: 99%
“…Although previous xPDT studies can be found in the literature [10][11][12][13][14][15][16][17][18][19][20], evaluating the role played by the photosensitizers in the presented results -specially the experimental ones -is a far from trivial task. Since information about the physical interactions between the x-rays and photosensitizers is sparse, and results in the absence of these photosensitizing agents are not always presented, numerically modelling and evaluating such interactions may provide useful information for optimizing the xPDT.…”
mentioning
confidence: 99%